CONCEPT OF SHADKRIYAKAALA OF VRANA BY SUSRUTHA W.S.R TO VENOUS ULCER - V.B. Binya; M.M.Abdul Shukkoor; N.H.Subi (International Journal of Ayurveda and Pharma Research, 2020)
Acharya Susrutha has described about the Samprapthi (pathogenesis) of Vrana (ulcer) in detail in Susrutha samhitha sutrasthana. All the ulcers like arterial ulcer, venous ulcer, trophic ulcer etc can be considered as Vrana. But no specific term has been made by Acharya for venous ulcer. Venous ulcers are the wounds occurring as a result of inappropriate functioning of venous valves or of venous obstruction by thrombus. While going through the characteristics of Dushtavrana (chronic ulcer) like Krishna/ Suklavarna (hyper/hypopigmented areas), Deerghakaala anubandhitwa (chronicity), Durgandhitha pooyasraava (foul smelling serous/ purulent discharge) etc, venous ulcer can be considered as a dushtavrana, particularly in its chronic stage. Sira (vein) is the deranged anatomical component in case of venous insufficiency as well as venous ulcer and this Sira has been told as one of the Vranasthaanaas (sites of Vrana) by Susrutha. Hence the term Sirajadushtavrana can be attributed to venous ulcer. Aetiopathogenesis of venous ulcer has striking similarities with that of Dushtavrana. In this article, a gentle attempt has been made to correlate the aetiopathogenesis of venous ulcer with the specific characteristics said in each stage of Shadkriyakala (aetiopathogenesis) of Vranasamprapthi (ulcer) as told by Acharya.